2016
DOI: 10.1038/emi.2016.1
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and characteristics of hypoxic hepatitis in the largest single-centre cohort of avian influenza A(H7N9) virus-infected patients with severe liver impairment in the intensive care unit

Abstract: Avian influenza A(H7N9) virus (A(H7N9)) emerged in February 2013. Liver impairment of unknown cause is present in 29% of patients with A(H7N9) infection, some of whom experience severe liver injury. Hypoxic hepatitis (HH) is a type of acute severe liver injury characterized by an abrupt, massive increase in serum aminotransferases resulting from anoxic centrilobular necrosis of liver cells. In the intensive care unit (ICU), the prevalence of HH is ∼1%–2%. Here, we report a 1.8% (2/112) incidence of HH in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…However, drug involvement was less likely in this case, as the proportion of eosinophils was not elevated and no typical histologic al findings of a druginduced liver injury, such as cholestasis, were observed. The typical histological characteristic of hypoxic hepatitis is centrilobular hepatocyte necrosis without prominent inflammation (3,8), which is consistent with the findings in this case.…”
supporting
confidence: 91%
“…However, drug involvement was less likely in this case, as the proportion of eosinophils was not elevated and no typical histologic al findings of a druginduced liver injury, such as cholestasis, were observed. The typical histological characteristic of hypoxic hepatitis is centrilobular hepatocyte necrosis without prominent inflammation (3,8), which is consistent with the findings in this case.…”
supporting
confidence: 91%
“…Further study found that Kupffer cells and apoptotic hepatocytes mediated inflammatory injury [18]. Hypoxic hepatitis was a clinical characteristic in the H7N9 infection [9]. Recent data further confirmed that hypoxic hepatitis can be an important causative factor for acute liver failure associated with influenza virus infection instead of virus related hepatitis [19].…”
Section: Discussionmentioning
confidence: 88%
“…A novel pandemic 2009 influenza A ⁄ H1N1 different from the seasonal influenza infection induced hepatocellular injury with increased serum aminotransaminase levels [6,7]. When humans are infected with H7N9, hypoxic and fatty changes in the liver tissue have been observed [8,9]. Moreover, in advanced chronic liver disease, diseases caused by the common bacteria Streptococcus pneumoniae or influenza virus increased the risk for serious health complications and death [10].…”
Section: Introductionmentioning
confidence: 99%
“… 2 Although previous studies have shown that H7N9 infection is often accompanied by multiple chronic conditions (hypertension, diabetes, chronic bronchitis, etc. ), 3 6 the most recent H7N9 epidemic seems to reveal a different increased risk of death in elderly patients with particular chronic underlying medical conditions (UMCs). 3 , 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…), 3 6 the most recent H7N9 epidemic seems to reveal a different increased risk of death in elderly patients with particular chronic underlying medical conditions (UMCs). 3 , 6 , 7 …”
Section: Introductionmentioning
confidence: 99%